Assessment of prevalence and gender distribution of hypodontia in maxillary dentition - SHAH, MILONI SURESH; SUBRAMANIAN, ARAVIND KUMAR; GOPAL, MARAGATHAVALLI (The journal of contemporary issues in business and government, 2020)
Congenitally missing teeth or as usually called hypodontia, is a highly prevalent and common developmental dental anomaly where there is congenital absence of one or more teeth. It is the most prevalent dental malformation in humans that could affect and influence the orthodontic diagnosis and treatment planning. Besides an unfavorable appearance, patients with missing teeth may suffer from malocclusion, periodontal damage, insufficient alveolar bone growth, reduced chewing ability, inarticulate pronunciation and other problems.The purpose of this retrospective study was to assess the prevalence and gender distribution of hypodontia in maxillary teeth, excluding the third molars. Orthopantomogram of orthodontic patients above the age group of 14 years were examined for evidence of hypodontia. The casts were used as an additional means of confirming the diagnosis. Retrospective data of patients were collected and those patients who had missing teeth were first segregated. From among those the patients details with congenitally missing teeth were then sorted. 15 patients with congenitally missing teeth excluding third molars were found fulfilling all the inclusion and exclusion criteria. The data was analysed using SPSS statistical software, descriptive and analytical statistics was done with Chi square test. It was observed that hypodontia of maxillary teeth was more predominant in maxillary lateral incisors (n- 12;80%)followed by maxillary premolars (n-2;13.4%) and canines(n=1;6.7%).Occurrence of hypodontia was more predominant in females(53.3%) when compared to males (46.7%) (p>0.05); hence statistically not significant. Early diagnosis and appropriate management might help in the attainment of ideal occlusion without the need for extensive orthodontic therapy